POSTPARTUM HEMORRHAGE IN SPONTANEOUS VERSUS INDUCED LABOR IN PRIMIGRAVIDA AT TERM - Shah, Shazma; Hayat, Nazish; Kishwar, Nasreen; Shah, Mehtab (Journal of Postgraduate Medical Institute, 2022)
Objectives: To compare the frequency of Postpartum Hemorrhage (PPH) in spontaneous Vs induced labor in Primigravidas at term. Methods: This was a comparative cross-sectional study, conducted in the Department of Obstetrics and Gynaecology, Hayatabad Medical Complex, and Lady Reading Hospital Peshawar. A total of 134 Primigravidas, were enrolled through non probability consecutive sampling after taking informed consent. PPH was noted for individual patients, who were grouped as those undergoing spontaneous labor and those entering labor after the process of induction with Misoprostol. All the data was entered and analyzed with the help of SPSS 21. Results: The study was conducted on 134 primigravida women subjected to either spontaneous or induced labor. The mean age of the whole study sample was 27.5 + 4.8 years. The mean BMI of the whole study sample was 22.3 + 1.7kg/m2. The sample of 134 women, 59.7% (n=80) were having spontaneous labor while 40.3% (n=54) were induced using Misoprostol. The overall frequency of PPH was recorded in 26.9% (n=36) of the sample. When stratified with regards to the mode of labor onset, it was found that there is a significant increase in the frequency of PPH in Primigravidas with induced labour. Conclusion: The frequency of PPH is significantly high in women who are subjected to induced labor as compared to spontaneous labor.